The Role of Regional Anaesthesia During and After COVID-19: A Safer Alternative to General Anaesthesia - Banu, Shaistha; Prapti Rath (Gayaku Publisher, 2024)
The COVID-19 pandemic has dramatically impacted surgical and anesthetic practice, challenging anesthesiologists to prioritize more emphasis on safer treatment methods. General anesthesia (GA) carries a high risk of virus transmission as it is associated with Aerosol-Generating Medical Procedures (AGMPs), such as tracheal intubation, which would subsequently spread the virus within health facilities. Anaesthesiology societies have strongly supported the use of regional anesthesia (RA) over GA for most patients, especially those with COVID-19. There are several advantages of RA: It minimizes exposure to aerosols, reduces the requirements for anesthetic agents, and has a lower rate of postoperative respiratory complications. Moreover, it preserves the immunological function of the patient and reduces demand for crucial resources, such as mechanical ventilation, thereby making it differently suitable for usage in global health emergencies. This review discusses the difficulties associated with GA during the pandemic. The review emphasizes on RA techniques such as ultrasound guidance and interfascial plane blocks. Choosing RA even in post COVID era is a choice, because it holds an advantageous risk-benefit profile and helps in the recovery of the patients.